A genotype-by-sequencing dataset and identity-by-state matrix of genetic variation in 821 Pinus radiata trees from 16 counties - Addison, Sarah L. (2025)
Pinus radiata D. Don is one of the most widely planted conifer species globally. While it holds major commercial importance as a softwood plantation tree, its native populations are endangered, making it a species of high conservation value. Here, we present a comprehensive dataset of genetic variation in P. radiata, derived from 821 trees (113 endemic and 708 introduced) sampled across 16 countries. These include both highly domesticated material used in commercial forestry and genetically unaltered individuals from endemic populations. Genotyping was performed using genotype-by-sequencing (GBS), also known as double-digest RAD sequencing (ddRADseq), from P. radiata needle-derived genomic DNA. Alongside the SNP-by-sample dataset, we provide an identity-by-state (IBS) matrix capturing genetic relatedness among individuals. These resources can help trace the genetic origins of current tree breeding selections, identify opportunities to introgress novel genetic material to improve form, growth, and resilience, understand invasiveness of the taxon and guide efforts in conservation and restoration while maintaining the genetic integrity of endemic populations of this globally important species.